Lossy mode resonance-based optical immunosensor towards detecting gliadin in aqueous solutions. (May 2023) - Benítez, M.; Zubiate, P.; Socorro-Leránoz, A.B.; Matias, I.R.
Abstract: The development of accurate, intuitive, and easy-to-handle devices to detect different types of allergens is on the rise, as these are useful tools to guarantee consumer safety, which should be a priority for any food industry. Gliadin, one of the main proteins present in gluten, is the one responsible for triggering the immune system to produce autoantibodies in celiac disease, the most dangerous pathology related to gluten. Lossy Mode Resonance (LMR) based biosensors are lately known as a promising sensing technology and its implementation on planar waveguides has been shown to result in manageable, sustainable and robust structures. In this work, an LMR based microfluidic biosensor for gliadin detection is proposed, by coating a coverslip with Titanium Dioxide (TiO2 ) by Atomic Layer Deposition (ALD) to generate the resonance phenomena and functionalizing the sensor surface with anti-gliadin antibody (AGA) through covalent bond. The sensor was exposed to different gliadin concentrations in ultrapure water, in the range of 0.1–100 ppm with an accuracy of ±0.14 ppm, for a sensitivity of 1.35 ppm/ml. The calibration curve was obtained from the experimental data corresponding to three repetitions of the assay and a limit of detection (LOD) of 0.05 ppm was achieved. Moreover, the sensor was exposed to commercial flour samples, some of them labeled as gluten free (GF) and the response agreed with the expected results according to product label. Biosensor specificity to gliadin was demonstrated by injecting chicken egg white albumin without obtaining any significant response. Highlights: An LMR based immunosensor on planar waveguide for gliadin detection is proposed. The gliadin biosensor is label-free and provides real time measurements. The gliadin concentration detection is 100 times below the gluten-free threshold. Easy and portable method to use in food industry when quantifying gluten proteins.